Oxygenated versus standard cold perfusion preservation in kidney transplantation (COMPARE): a randomised, double-blind, paired, phase 3 trial. Issue 10263 (21st November 2020) - Jochmans, Ina; Brat, Aukje; Davies, Lucy; Hofker, H Sijbrand; van de Leemkolk, Fenna E M; Leuvenink, Henri G D; Knight, Simon R; Pirenne, Jacques; Ploeg, Rutger J; ,; Abramowicz, Daniel; Banga, Neal; et al.
Summary: Background: Deceased donor kidneys are preserved in cold hypoxic conditions. Providing oxygen during preservation might improve post-transplant outcomes, particularly for kidneys subjected to greater degrees of preservation injury. This study aimed to investigate whether supplemental oxygen during hypothermic machine perfusion (HMP) could improve the outcome of kidneys donated after circulatory death. Methods: This randomised, double-blind, paired, phase 3 trial was done in 19 European transplant centres. Kidney pairs from donors aged 50 years or older, donated after circulatory death, were eligible if both kidneys were transplanted into two different recipients. One kidney from each donor was randomly assigned using permuted blocks to oxygenated hypothermic machine perfusion (HMPO2 ), the other to HMP without oxygenation. Perfusion was maintained from organ retrieval to implantation. The primary outcome was 12-month estimated glomerular filtration rate (eGFR) using the Chronic Kidney Disease Epidemiology Collaboration equation in pairs of donated kidneys in which both transplanted kidneys were functioning at the end of follow-up. Safety outcomes were reported for all transplanted kidneys. Intention-to-treat analyses were done. This trial is registered with the ISRCTN Registry, ISRCTN32967929, and is now closed. Findings: Between March 15, 2015, and April 11, 2017, 197 kidney pairs were randomised with 106 pairs transplanted into eligible recipients. 23 kidney pairs were excluded from the primary analysis because of kidney failure or patient death. Mean eGFR at 12 months was 50·5 mL/min per 1·73 m 2 (SD 19·3) in the HMPO2 group versus 46·7 mL/min per 1·73m 2 (17·1) in HMP (mean difference 3·7 mL/min per 1·73m 2, 95% CI −1·0 to 8·4; p=0·12). Fewer severe complications (Clavien-Dindo grade IIIb or more) were reported in the HMPO2 group (46 of 417, 11%, 95% CI 8% to 14%) than in the HMP group (76 of 474, 16%, 13% to 20%; p=0·032). Graft failure was lower with HMPO2 (three [3%] of 106) compared with HMP (11 [10%] of 106; hazard ratio 0·27, 95% CI 0·07 to 0·95; p=0·028). Interpretation: HMPO2 of kidneys donated after circulatory death is safe and reduces post-transplant complications (grade IIIb or more). The 12-month difference in eGFR between the HMPO2 and HMP groups was not significant when both kidneys from the same donor were still functioning 1-year post-transplant, but potential beneficial effects of HMPO2 were suggested by analysis of secondary outcomes. Funding: European Commission 7th Framework Programme.